2010
DOI: 10.1111/j.1365-2907.2009.00154.x
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography of common dolphins (genus Delphinus) in the Southwestern Atlantic Ocean

Abstract: 1. The common dolphins (genus Delphinus) have one of most problematic taxonomies and complex distribution patterns of all cetaceans. Although the taxonomy and the distribution seem to have been clarified somewhat in the eastern North Pacific and Indo-Pacific Oceans, many questions remain in the Southwestern Atlantic Ocean (SWA). We review the biogeography of Delphinus in the SWA. 2. We reviewed data from strandings, incidental catches and sightings since 1922. Systematic surveys were conducted in five major ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 41 publications
(79 reference statements)
3
43
1
1
Order By: Relevance
“…With the discovery of a main breeding area off southern Brazil (~27 o S) (OTT et al, 2008), the recovery of the right whale population from past exploitation may be expanding the breeding area to include protected bays in southeastern Brazil. The northern coast of SP state has shallow protected bays which have been used by female-calf pairs during the last 20 years (see LODI et al, 1996;SANTOS et al, 2001a (see ZERBINI et al, 2004;MORENO et al, 2005;TAVARES et al, 2010), as well as for the higher incidence of these species' strandings. A few records have related to strays from their currently known range -such as B. arnuxii, M. europaeus and L. peronii.…”
Section: Discussionmentioning
confidence: 99%
“…With the discovery of a main breeding area off southern Brazil (~27 o S) (OTT et al, 2008), the recovery of the right whale population from past exploitation may be expanding the breeding area to include protected bays in southeastern Brazil. The northern coast of SP state has shallow protected bays which have been used by female-calf pairs during the last 20 years (see LODI et al, 1996;SANTOS et al, 2001a (see ZERBINI et al, 2004;MORENO et al, 2005;TAVARES et al, 2010), as well as for the higher incidence of these species' strandings. A few records have related to strays from their currently known range -such as B. arnuxii, M. europaeus and L. peronii.…”
Section: Discussionmentioning
confidence: 99%
“…This area is under the domain of the high pressure center of the Atlantic anticyclone which controls the climate and determines the large-scale oceanographic circulation. The main currents of the SWA are the South Equatorial, Brazil and Malvinas Currents (Moreno et al, 2005;Seeliger et al, 1997;Tavares et al, 2010).…”
Section: Study Areamentioning
confidence: 98%
“…Considering the large cetaceans dispersal ability and not obvious geographical barriers to dolphins, the geographical extent of the models and the background sampling was restrict to the SWA, which comprises waters south of Equator and west of 20°W (Moreno et al, 2005;Tavares et al, 2010). This area is under the domain of the high pressure center of the Atlantic anticyclone which controls the climate and determines the large-scale oceanographic circulation.…”
Section: Study Areamentioning
confidence: 99%
“…Elsewhere in the world there are long-beaked populations (of the 'capensis' type) proposed to occur off Peru, Chile, Venezuela, Brazil, Argentina, South Africa, Madagascar, India, Indonesia, China, Korea and southern Japan (see Hammond et al, 2008;Jefferson et al, 2008), although for a number of these locations occurrence is not well documented. Based on the 'rostral index' (rostrum length/zygomatic width ratio, see below), Cunha et al (2015) identified 5 'delphis' and 9 'capensis' types off Brazil and Argentina among the 14 skulls they measured, and Tavares et al (2010) identified 47 of 59 measured skulls from this region as the 'capensis' type. However, Cunha et al (2015) suggest that D. capensis should not be used to refer to the long-beaked form, and instead the lbENP form should again be recognized as D. bairdii and all other populations recognized as D. delphis.…”
Section: Introductionmentioning
confidence: 99%